Soil Productivity Enhancement - Nuhu Issaka, Roland; Moro Buri, Mohammed (IntechOpen, 2018)
Soil Productivity Enhancement comprises five chapters written by scientists from various parts of the world. The book is divided into three sections. 1: Conversion of Environmentally Polluting Waste into Fertilizer. This section discusses the conversion of waste water and other by-products from factories into organic fertilizers. It further examines how these materials can be used to enhance crop production and improve soil productivity. 2: Practices for Improving Nutrient Availability. Good nutrient management and proper composting of organic materials are options that can be used to enhance the productivity of soil. These and other practices are examined in this section. 3: Policy on Fertilizer Use. The need for effective policies to control and promote the effective and efficient use of fertilizers is discussed in this section.